2001
DOI: 10.1177/000348940111000403
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Progressive Subglottic Stenosis: Findings and Treatment in 52 Patients

Abstract: Rarely, patients develop severe idiopathic subglottic stenosis. In 34 years, we have observed this disorder in 52 patients. All but 1 of the patients were female--a finding that suggests a hormonal cause. Without treatment, the airway progressively narrows--in some cases, until the patient requires tracheotomy. Laser submucosal resection and rotation mucosal flaps open and stabilize the airway and provide effective palliation. However, unlike traumatic subglottic stenosis, which has been cured with this techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 14 publications
(1 reference statement)
4
127
0
3
Order By: Relevance
“…As in other studies [13, 8, 1114], this study demonstrated homogeneity among ISS patients, who were mainly healthy females of European descent, diagnosed in their 50 s and requiring multiple procedures. The pathophysiology of the condition is unclear, but the age at diagnosis of approximately 50 years coincides with onset of menopause, supporting the hypothesis that hormones influence the etiologic process [1, 4, 11, 15].…”
Section: Discussionsupporting
confidence: 86%
“…As in other studies [13, 8, 1114], this study demonstrated homogeneity among ISS patients, who were mainly healthy females of European descent, diagnosed in their 50 s and requiring multiple procedures. The pathophysiology of the condition is unclear, but the age at diagnosis of approximately 50 years coincides with onset of menopause, supporting the hypothesis that hormones influence the etiologic process [1, 4, 11, 15].…”
Section: Discussionsupporting
confidence: 86%
“…The accuracy of their diagnoses is questionable as idiopathic subglottic stenosis in females is a well-recognised entity. [9][10][11] In the oldest paper, written by Spraggs et al, the authors describe two patients who received either laryngotracheoplasty or laryngotracheal reconstruction. 12 The first patient received multiple previous surgical interventions before finally undergoing laryngotracheoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der idiopathischen subglottischen Stenose kommt es ohne erkennbare Ursache zur Ausbildung einer submukösen Fibrose. Das patho gnomonische Merkmal der idiopathischen subglottischen Stenose ist eine submuköse Verdickung des Bindegewebes mit Zeichen von chronischer Entzün-dung [5].…”
Section: Subglottische Trachealstenosenunclassified
“…Bei 6 der 15 Patienten war nur eine Behandlung notwendig. Bei den restlichen 9 Patienten war eine weitere Nachbehandlung in einem durchschnittlichen Intervall von 9 Monaten erforderlich.In der Arbeit von Dedo u. Catten[5] wurden 52 Patienten mit idiopathischer Trachealstenose in einem Zeitraum von 34 Jahren beurteilt. 51 der 52 Patienten waren Frauen, was auf eine hormonelle Ursache der Erkrankung hinweist.…”
unclassified